www.sudacon.net for construction news in Sudan - Abdelatif, Amged O. (sudacon, 2012)
www.sudacon.net is a website created by Dr. Amged O. Abdelatif, a Research Fellow at the University of Nottingham, Civil Engineering Department. The website concerns the latest news in the construction sector in Sudan. It provides an update of the labor and material prices, jobs, tenders/bids, and other related topic. The website also represents a platform for the FixKhartoum project. This project is acting as a tool to report issues in roads and streets such as pothole problems, lighting problems, and leakages.